A novel missense variant of SCN4A co‐segregates with congenital essential tremor in a consanguineous Kurdish family. Issue 4 (16th December 2021) - Asif, Maria; Mocanu, Ionut Dragos; Abdullah, Uzma; Höhne, Wolfgang; Altmüller, Janine; Makhdoom, Ehtisham Ul Haq; Thiele, Holger; Baig, Shahid Mahmood; Nürnberg, Peter; Graul‐Neumann, Luitgard; Hussain, Muhammad Sajid
Abstract: Essential tremor (ET) is a neurological disorder characterized by bilateral and symmetric postural, isometric, and kinetic tremors of forelimbs produced during voluntary movements. To date, only a single SCN4A variant has been suggested to cause ET. In continuation of the previous report on the association between SCN4A and ET in a family from Spain, we validated the pathogenicity of a novel SCN4A variant and its involvement in ET in a second family affected by this disease. We recruited a Kurdish family with four affected members manifesting congenital tremor. Using whole‐exome sequencing, we identified a novel missense variant in SCN4A, NM_000334.4:c.4679C>T; p.(Pro1560Leu), thus corroborating SCN4A's role in ET. The residue is highly conserved across vertebrates and the substitution is predicted to be pathogenic by various in silico tools. Western blotting and immunocytochemistry performed in cells derived from one of the patients showed reduced immunoreactivity of SCN4A as compared to control cells. The study provides supportive evidence for the role of SCN4A in the etiology of ET and expands the phenotypic spectrum of channelopathies to this neurological disorder.